Eugenol potentiates cisplatin anti‐cancer activity through inhibition of ALDH‐positive breast cancer stem cells and the NF‐κB signaling pathway. Issue 3 (24th November 2017) - Islam, Syed S.; Al‐Sharif, Ibtehaj; Sultan, Ahlam; Al‐Mazrou, Amer; Remmal, Adnane; Aboussekhra, Abdelilah
Abstract : Triple‐negative breast tumors are very aggressive and contain relatively high proportion of cancer stem cells, and are resistant to chemotherapeutic drugs including cisplatin. To overcome these limitations, we combined eugenol, a natural polyphenolic molecule, with cisplatin to normalize cisplatin mediated toxicity and potential drug resistance. Interestingly, the combination treatment provided significantly greater cytotoxic and pro‐apoptotic effects as compared to treatment with eugenol or cisplatin alone on several triple‐negative breast cancer cells both in vitro and in vivo. Furthermore, adding eugenol to cisplatin potentiated the inhibition of breast cancer stem cells by inhibiting ALDH enzyme activity and ALDH‐positive tumor initiating cells. We provide also clear evidence that eugenol potentiates cisplatin inhibition of the NF‐κB signaling pathway. Indeed, the binding of NF‐κB to its cognate binding sites present in the promoters of IL‐6 and IL‐8 was dramatically reduced, which led to potent down‐regulation of the IL‐6 and IL‐8 cytokines upon combination treatment relative to the single agents. Similar effects were observed on proliferation, inhibition of epithelial‐to‐mesenchymal transition and stemness markers in tumor xenografts. These results provide strong preclinical justification for combining cisplatin with eugenol as therapeutic approach for triple‐negative breast cancers through targeting the resistant ALDH‐positive cells and inhibiting the NF‐κB pathway.